A Scoping Review of Social Support Interventions with Refugees in Resettlement Contexts: Implications for Practice and Applied Research. Issue 4 (2nd October 2021) - Wachter, Karin; Dalpe, Jessica; Bonz, Annie; Drozdowski, Hayley; Hermer, Janice
Abstract: Profound consequences of forced migration include the destruction of social networks and loss of social support. This scoping review examined the landscape of interventions that promote social support among refugees in resettlement contexts. Findings from the analysis revealed the extent to which social support intervention research is a relatively nascent area of practice and research. The analysis also revealed creative innovations in intervention design and research. These innovations serve as a springboard for envisioning a new generation of programs and scholarship that acknowledge and substantively address needs for social connections among refugees in resettlement.